Closed-Vessel Conductively Heated Digestion System for the Elemental Analysis of Agricultural Materials by High-Resolution Continuum Source Flame Atomic Absorption Spectrometry (HR-CS FAAS) - Traversa, Leonardo Clemente [UNESP]; Santiago, João Victor Biagi [UNESP]; de Oliveira, Evilim Martinez [UNESP]; Ferreira, Edilene Cristina [UNESP]; Virgilio, Alex; Gomes Neto, José Anchieta [UNESP] (Taylor & Francis, 2023)
Novel applications of the closed-vessel conductively heated digestion system (CHDS) are proposed to digest biomass, biochar, oyster shell flour, bone meal and swine manure for the determination of Ca, K, Mg, Na, Cu, Fe, Mn, and Zn by high-resolution continuum source flame atomic absorption spectrometry (HR-CS FAAS). The performance of the digestion method using 14 and 7 mol L−1 HNO3 was checked by analyzing soil, rock, and plant certified reference materials (CRMs). For comparative purposes, all samples were analyzed after microwave-assisted digestion (MW-AD). Results obtained for most analytes by the closed-vessel conductively heated digestion system (CHDS) were in agreement with certified values and those attained by the comparative digestion method. The use of 7 mol L−1 HNO3 furnished lower blanks for most analytes and was effective to prepare challenging samples as biomass, biochar, shell and bone meal, swine manure, plants, soil, phosphate rock, and may be a good alternative for elemental determinations using most analytical techniques that rely on solution-based sample introduction systems. The detection limits (dry basis, mg kg−1) for Ca, Cu, Fe, K, Mg, Mn, Na, and Zn were 3, 0.4, 4, 4, 0.7, 0.4, 3, and 2, respectively. The mean relative standard deviations were close to 4.9% for closed-vessel conductively heated digestion (CHDS) and 5.9% for microwave-assisted digestion (MW-AD).
Keywords: Agriculture materials; closed-vessel conductively heated digestion system (CHDS); high-resolution continuum source flame atomic absorption spectrometry (HR-CS FAAS)